Laminate and packaging container

JP7631670B2Active Publication Date: 2025-02-19DAI NIPPON PRINTING CO LTD

Patent Information

Application Number
JP2020063340
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-02-19
Estimated Expiration
2040-03-31

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、モノマテリアル包装容器の作製に好適に使用することができ、蒸着膜との層間の密着性を顕著に向上することができ、好ましいガスバリア性を達成することができる、積層体を提供することができる。 また、本発明によれば、積層体からなる包装容器を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631670000002
    Figure 0007631670000002
  • Figure 0007631670000003
    Figure 0007631670000003
  • Figure 0007631670000004
    Figure 0007631670000004
Patent Text Reader

Abstract

To provide a laminate favorably usable for producing a mono-material packaging container, with high adhesion to a vapor-deposited film, and capable of effectively preventing delamination when made into a packaging container.SOLUTION: A laminate at least includes a first sealant layer, a vapor-deposited film and a second sealant layer sequentially. The first sealant layer at least includes a polyethylene resin layer and a surface resin layer. The second sealant layer is composed of a polyethylene. The surface resin layer of the first sealant layer includes a resin material with a melting point 150°C or higher. The vapor-deposited film is disposed on the surface resin layer of the first sealant layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a packaging container. [Background technology]

[0002] Conventionally, resin films made of polyester resins such as polyethylene terephthalate (hereinafter also referred to as polyester films) have been used as substrates constituting laminates used in the manufacture of packaging containers because they are excellent in mechanical properties, chemical stability, heat resistance and transparency, and are inexpensive.

[0003] Such polyester films are usually laminated with a polyethylene film, which is a sealant layer, to form a laminate, which is then formed into a packaging container.

[0004] The packaging containers made from the above-mentioned laminate of different resin films, i.e., a polyester film and a polyethylene film, are difficult to separate into their respective layers, and packaging containers collected after use are not suitable for recycling, and therefore are not actively recycled.

[0005] In order to improve the recyclability of packaging containers, studies are being conducted on the production of packaging containers using laminates made of the same material (mono-material packaging containers) using polyester films instead of polyester films. Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, the inventors attempted to form a vapor-deposited film on the surface of the polyethylene film, which serves as a sealant layer, in order to compensate for the reduced gas barrier properties that result from changing from polyester film to polyethylene film. However, they discovered a new problem in that the adhesion between the polyethylene film and the vapor-deposited film was insufficient, and when a packaging container was produced using the polyethylene film on which the vapor-deposited film had been formed, there was a risk of delamination occurring between the polyethylene film and the vapor-deposited film.

[0007] And, surprisingly, the inventors discovered that by providing a surface resin layer containing a resin material having a melting point of 150°C or higher on the surface of a polyethylene film, the adhesion of a vapor-deposited film formed on the surface resin layer is improved, and as a result, the gas barrier properties of the laminate are significantly improved, thereby solving the above-mentioned problems.

[0008] The present invention has been made based on such findings, and the problem to be solved by the present invention is to provide a laminate that can be suitably used for producing mono-material packaging containers, has high adhesion to a vapor deposition film, and can effectively prevent delamination when used as a packaging container.

[0009] Another problem to be solved by the present invention is to provide a packaging container made of the above-mentioned laminate. [Means for solving the problem]

[0010] The laminate of the present invention is a laminate including at least a first sealant layer, a vapor-deposited film, and a second sealant layer in this order, the first sealant layer comprises at least a polyethylene resin layer and a surface resin layer; the second sealant layer is made of a polyethylene resin; the surface resin layer of the first sealant layer contains a resin material having a melting point of 150° C. or more; The vapor-deposited film is characterized in that it is provided on a surface resin layer of the first sealant layer.

[0011] In one embodiment, the surface resin layer contains a resin material having a melting point of 150° C. or higher and 265° C. or lower.

[0012] In one embodiment, the melting point difference between the polyethylene resin and the resin material having a melting point of 150°C or more contained in the surface resin layer is 20 to 80°C.

[0013] In one embodiment, the resin material of the surface resin layer is made of a polymer having a polar group.

[0014] In one embodiment, the resin material of the surface resin layer is one or more resin materials selected from ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyester, nylon 6, nylon 6,6, nylon 6-nylon 6,6 copolymer, MXD nylon, and amorphous nylon.

[0015] In one embodiment, the polyethylene resin layer of the first sealant layer has a multi-layer structure.

[0016] In one embodiment, the polyethylene resin layer of the first sealant layer comprises at least one layer comprising a compatibilizer.

[0017] In one embodiment, the first sealant layer is a co-extruded film.

[0018] In one embodiment, the coating further comprises a barrier coat layer between the vapor-deposited film and the second sealant layer.

[0019] In one embodiment, the laminate is used in a packaging container.

[0020] In one embodiment, the content of the polyethylene resin in the entire laminate is 95 mass % or more.

[0021] The packaging container of the present invention comprises the above laminate.

[0022] In one embodiment, the packaging container is a laminate tube. Effect of the Invention

[0023] According to the present invention, it is possible to provide a laminate which can be suitably used for producing a mono-material packaging container, which can significantly improve the adhesion between the layer and the vapor-deposited film, and which can achieve favorable gas barrier properties. Furthermore, according to the present invention, a packaging container made of the laminate can be provided. [Brief description of the drawings]

[0024] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a deposition apparatus. [Diagram 3] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a deposition apparatus. [Figure 4] 1 is a front view showing a laminate tube which is one embodiment of a packaging container of the present invention. [Diagram 5] 5 is a cross-sectional view of FIG. 4 taken along line aa. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] (Laminate) 1, a laminate 10 of the present invention comprises, in order, at least a first sealant layer 11, a vapor-deposited film 12, and a second sealant layer 13. The first sealant layer 11 comprises at least a polyethylene resin layer 14 and a surface resin layer 15. The vapor-deposited film 12 is provided on the surface resin layer 15 of the first sealant layer 11. The laminate of the present invention includes a polyethylene resin layer and a second sealant layer made of a polyethylene resin. Such a laminate can be suitably used as a laminate for producing a mono-material packaging container. Furthermore, the laminate of the present invention has significantly improved interlayer adhesion between the sealant layer and the vapor-deposited film, and has extremely high gas barrier properties.

[0026] The first sealant layer 11 may include an adhesive resin layer between the polyethylene resin layer 14 and the surface resin layer 15 (not shown).

[0027] In one embodiment, the laminate 10 may include a melt extruded resin or adhesive layer 16 between the vapor deposited film 12 and the second sealant layer 13 .

[0028] The content of the polyethylene resin in the total amount of solids contained in the laminate is preferably 95% by mass or more, which makes the laminate suitable for use in producing mono-material packaging containers.

[0029] Each layer of the laminate 10 will now be described.

[0030] (First sealant layer) The first sealant layer includes at least a polyethylene resin layer and a surface resin layer, and in one embodiment, the first sealant layer includes an adhesive resin layer between the polyethylene resin layer and the surface resin layer.

[0031] The ratio of the thickness of the surface resin layer to the total thickness of the first sealant layer is preferably 1% or more and 20% or less, and more preferably 2% or more and 10% or less. By setting the ratio of the thickness of the surface resin layer to the total thickness of the first sealant layer to be 1% or more, the adhesion of the vapor-deposited film can be further improved, and the gas barrier properties can be further improved. In addition, by setting the ratio of the thickness of the surface resin layer to the total thickness of the first sealant layer to 20% or less, a laminate that can be suitably used for producing mono-material packaging containers can be obtained. Furthermore, the film-forming property and processability of the sealant layer can be further improved.

[0032] (Polyethylene resin layer) In the present invention, the term "polyethylene resin layer" refers to a layer made of a polyethylene resin. As the polyethylene resin, high density polyethylene resin (HDPE), medium density polyethylene resin (MDPE), low density polyethylene resin (LDPE), linear low density polyethylene resin (LLDPE) and very low density polyethylene resin (VLDPE) can be used. Moreover, as the polyethylene resin, a copolymer of ethylene and another monomer can also be used. Furthermore, as the polyethylene resin, a biomass-derived polyethylene resin or a mechanically recycled or chemically recycled polyethylene resin can also be used.

[0033] Here, the high density polyethylene resin has a density of 0.945 g / cm 3 The polyethylene resins used are those with a density of 0.930 g / cm or more. Medium density polyethylene resins are those with a density of 0.930 g / cm or more. 3 More than 0.945g / cm 3 A polyethylene resin having a density of less than 0.900 g / cm can be used. 3 More than 0.930g / cm 3 A polyethylene resin having a density of less than 0.900 g / cm can be used. As a linear low-density polyethylene resin, a polyethylene resin having a density of less than 0.900 g / cm can be used. 3 More than 0.930g / cm 3 For ultra-low density polyethylene resin, a polyethylene resin with a density of 0.900 g / cm3 or less can be used. 3 Polyethylene resins less than 100% may be used.

[0034] The content of the polyethylene resin in the polyethylene resin layer is preferably 70% by mass or more, and more preferably 80% by mass or more, which allows the laminate of the present invention to be more suitably used for producing a mono-material packaging container.

[0035] The polyethylene resin layer included in the first sealant layer may have a single-layer structure or a multi-layer structure.

[0036] In one embodiment, the polyethylene resin layer may include at least one layer including a compatibilizer. By including a compatibilizer in the polyethylene resin layer, when a packaging container made using the laminate of the present invention is heated and melted for recycling, the resin material having a melting point of 150° C. or more contained in the surface resin layer and the polyethylene resin constituting the polyethylene resin layer are uniformly mixed together, which effectively prevents the physical properties from being deteriorated and the transparency from being deteriorated. In addition, when the polyethylene resin layer has a multi-layer structure, the compatibilizer is preferably contained in a layer in contact with the surface resin layer of the polyethylene resin layer. By containing the compatibilizer in the layer in contact with the surface resin layer of the polyethylene resin layer, the above-mentioned effect can be further improved.

[0037] The compatibilizer may be appropriately selected from conventionally known ones and used. From the viewpoint of recyclability, however, unsaturated carboxylic acid modified polyolefin resins are preferred, and among them, maleic anhydride modified polyethylene resins are more preferred.

[0038] The content of the compatibilizer in the layer containing the compatibilizer is preferably 5% by mass or more and 30% by mass or less. By setting the content of the compatibilizer in the polyethylene resin layer to 5% by mass or more, the above-mentioned effects can be further improved. By setting the content of the compatibilizer in the polyethylene resin layer to 30% by mass or less, the strength and heat resistance of the first sealant layer can be improved.

[0039] As long as the properties of the present invention are not impaired, the polyethylene resin layer may contain a resin material other than polyethylene resin, for example, polyolefin resins such as polypropylene resin, (meth)acrylic resins, vinyl resins, cellulose resins, polyamide resins, polyester resins, and ionomer resins. From the viewpoint of recyclability, it is particularly preferable that the polyethylene resin layer does not contain any resin other than polyethylene resin.

[0040] Furthermore, to the extent that the characteristics of the present invention are not impaired, the polyethylene resin layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0041] In one embodiment, the polyethylene resin layer includes a layer made of a linear low-density polyethylene resin, a layer made of a high-density polyethylene resin, and a layer made of a linear low-density polyethylene resin. By adopting such a configuration, it is possible to improve heat sealability and strength.

[0042] The thickness of the polyethylene resin layer is preferably 50 μm or more and 200 μm or less, and more preferably 70 μm or more and 150 μm or less. By making the thickness of the polyethylene resin layer 50 μm or more, the laminate strength of the packaging container can be further improved. Furthermore, by setting the thickness of the polyethylene resin layer to 200 μm or less, the moldability of the laminate can be improved, and the packaging container can be produced more easily.

[0043] The polyethylene resin layer may have a printed layer on its surface. The image formed on the printed layer is not particularly limited, and may be a letter, a pattern, a symbol, or a combination thereof. The printing layer on the polyethylene resin layer can be formed using ink derived from biomass, which reduces the environmental impact. The method for forming the printed layer is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing.

[0044] (Surface resin layer) The first sealant layer of the laminate of the present invention comprises a surface resin layer on a polyethylene resin layer, the surface resin layer containing a resin material having a melting point of 150° C. or higher (hereinafter sometimes referred to as a high melting point resin material).

[0045] The melting point of the high melting point resin material is more preferably 160° C. or higher. By setting the melting point of the high melting point resin material to 160° C. or higher, the adhesion of the deposited film can be further improved, and the gas barrier properties can be further improved.

[0046] The melting point of the high-melting-point resin material is preferably 265° C. or less, more preferably 260° C. or less, and even more preferably 250° C. or less. By setting the melting point of the high-melting-point resin material to 265° C. or less, the film-forming properties of the first sealant layer can be improved.

[0047] The difference between the melting point of the high melting point resin material contained in the surface resin layer and the melting point of the polyethylene resin constituting the polyethylene resin layer is preferably 20 to 80°C, and more preferably 20 to 60°C. By setting the difference in melting point between the high-melting point resin material contained in the surface resin layer and the melting point of the polyethylene constituting the polyethylene resin layer to be 20°C or more, the adhesion of the vapor-deposited film can be further improved, and the gas barrier properties of the first sealant layer on which the vapor-deposited film is formed can be further improved. In addition, by having the difference between the melting point of the high-melting point resin material contained in the surface resin layer and the melting point of the polyethylene constituting the polyethylene resin layer be 80°C or less, the film-forming properties of the first sealant layer can be further improved.

[0048] In one embodiment, the high melting point resin material is made of a polymer having a polar group. By making the high melting point resin material a polymer having a polar group, the adhesion to the vapor-deposited film can be further improved.

[0049] In the present invention, the polar group refers to a group containing one or more heteroatoms, and examples thereof include an ester group, an epoxy group, a hydroxyl group, an amino group, an amide group, a carboxyl group, a carbonyl group, a carboxylic anhydride group, a sulfone group, a thiol group, and a halogen group. Among these, from the viewpoint of the laminate strength of the packaging container, a hydroxyl group, an ester group, an amino group, an amide group, a carboxyl group and a carbonyl group are preferred, and a hydroxyl group is more preferred.

[0050] Examples of high melting point resin materials include vinyl resins, polyamides, polyimides, polyesters, (meth)acrylic resins, cellulose resins, polyolefin resins, and ionomer resins.

[0051] In the present invention, a resin material having a melting point of 150°C or higher and having a polar group is particularly preferred, and amide resins such as ethylene-vinyl alcohol copolymers, polyvinyl alcohol, nylon 6, nylon 6,6, nylon 6-nylon 6,6 copolymers, MXD nylon, and amorphous nylon are preferred, with ethylene-vinyl alcohol copolymers and amide resins being particularly preferred. By using such a resin material, the adhesion of the evaporated film formed on the surface resin layer can be significantly improved, and the gas barrier properties can be effectively improved.

[0052] The content of the high melting point resin material in the surface resin layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. By making the content of the high melting point resin material in the surface resin layer 70% by mass or more, the adhesion of the vapor deposition film formed on the surface resin layer can be significantly improved, and the gas barrier property of the sealant layer on which the vapor deposition film is formed can be effectively improved.

[0053] As long as the characteristics of the present invention are not impaired, the surface resin layer may contain a resin material other than the high melting point resin material. From the viewpoint of adhesion to the evaporated film, it is preferable that the surface resin layer does not contain any resin material other than the high melting point resin material.

[0054] Furthermore, within the scope of not impairing the characteristics of the present invention, the surface resin layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0055] The thickness of the surface resin layer is preferably 0.1 μm or more and 5 μm or less, and more preferably 0.1 μm or more and 4 μm or less. By making the thickness of the surface resin layer 0.1 μm or more, the adhesion of the vapor-deposited film can be further improved, and the gas barrier property of the first sealant layer on which the vapor-deposited film is formed can be further improved. Moreover, by setting the thickness of the surface resin layer to 5 μm or less, the first sealant layer can be made suitable for use in the production of mono-material packaging containers, and the film-forming properties and processability of the first sealant layer can be further improved.

[0056] The surface resin layer of the first sealant layer may be subjected to a surface treatment, which can improve adhesion to adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0057] (adhesive resin layer) In one embodiment, an adhesive resin layer can be provided between the polyethylene resin layer and the surface resin layer of the first sealant layer, thereby improving the adhesion between these layers.

[0058] The adhesive resin layer can be formed by using an adhesive resin such as polyether, polyester, silicone resin, epoxy resin, polyurethane, vinyl resin, phenol resin, and polyolefin. Among the above, polyolefins and acid-modified products thereof are preferred, and polyethylene and acid-modified products thereof are particularly preferred, because the laminate of the present invention can be made into a configuration more suitable for mono-material packaging containers. As the adhesive polyethylene, commercially available products can be used, for example, the Admer series manufactured by Mitsui Chemicals, Inc. can be used.

[0059] The thickness of the adhesive resin layer is not particularly limited, but may be, for example, 1 μm or more and 15 μm or less. By making the thickness of the adhesive resin layer 1 μm or more, the adhesion between the polyethylene resin layer and the surface resin layer can be further improved. By making the thickness of the adhesive layer 15 μm or less, the processability of the first sealant layer can be improved.

[0060] In one embodiment, the first sealant layer is a co-extrusion film, and can be produced by film formation using a T-die method, an inflation method, or the like.

[0061] (evaporated film) The laminate of the present invention has a vapor-deposited film on and adjacent to a surface resin layer, and the vapor-deposited film and the surface resin layer have high adhesion to each other, and have extremely high gas barrier properties, specifically oxygen barrier properties and water vapor barrier properties. Furthermore, since the laminate has a vapor-deposited film, a packaging container produced using the laminate can suppress a loss in mass of the contents filled therein.

[0062] The vapor-deposited film may be a vapor-deposited film of one or more inorganic substances or inorganic oxides such as silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), etc. The vapor-deposited film may be composed of two or more layers, which may be composed of the same material or different materials. Among the above, from the viewpoints of adhesion to the surface resin layer and gas barrier properties, the vapor deposition film is preferably composed of aluminum, aluminum oxide (alumina) or silicon oxide (silica). In addition, by using a vapor deposition film composed of aluminum, the glossiness of the packaging container can be improved, and the design of the packaging container can be improved.

[0063] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0064] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. Moreover, by setting the thickness of the vapor-deposited film to 150 nm or less, a laminate that can be suitably used for producing mono-material packaging containers can be obtained, and further, the occurrence of cracks in the vapor-deposited film can be prevented.

[0065] The method for forming the vapor-deposited film may be a conventional method, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical vapor deposition method (CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, or a photochemical vapor deposition method. Hereinafter, one embodiment of the method for forming the evaporated film will be described, but the method for forming the evaporated film is not limited thereto.

[0066] As an apparatus used in the method for forming a vapor-deposited film by the PVD method, a plasma-assisted vacuum film-forming apparatus can be used. An embodiment of a method for forming a vapor-deposited film using a plasma-assisted vacuum film-forming apparatus will be described below. In one embodiment, the vacuum deposition apparatus includes a vacuum container A, a first sealant layer 11, an unwinding section B, a deposition drum C, a winding section D, a transport roll E, an evaporation source F, a reactive gas supply section G, an adhesion-proof box H, a deposition material I, and a plasma gun J, as shown in Figures 2 and 3. 2 is a schematic cross-sectional view of the vacuum film-forming apparatus in the XZ plane, and FIG. 3 is a schematic cross-sectional view of the vacuum film-forming apparatus in the XY plane. 2, the first sealant layer 11 wound around the film-forming drum C is placed with its surface resin layer surface facing downward in the upper part of the vacuum container A, and an electrically grounded deposition protection box H is placed below the film-forming drum C in the vacuum container A. An evaporation source F is placed on the bottom surface of the deposition protection box H. The film-forming drum C is placed in the vacuum container A so that the surface resin layer surface of the first sealant layer 11 wound around the film-forming drum C is located at a position facing the upper surface of the evaporation source F with a certain gap therebetween. In addition, transport rolls E are disposed between the unwinding section B and the film-forming drum C, and between the film-forming drum C and the winding section D. The vacuum vessel is connected to a vacuum pump (not shown). The evaporation source F is for holding the evaporation material I, and is equipped with a heating device (not shown). The reactive gas supply unit G is a portion that supplies a reactive gas (such as oxygen, nitrogen, helium, argon, and a mixture of these gases) that reacts with the evaporated deposition material. The vapor deposition material I is heated and evaporated from the evaporation source F and directed onto the surface resin layer of the first sealant 11, and at the same time, plasma is also directed from the plasma gun J toward the surface resin layer, forming a vapor deposition film. The details of this formation method are disclosed in JP 2011-214089 A.

[0067] As the plasma generating device used in the plasma chemical vapor deposition method, a device generating high frequency plasma, pulse wave plasma, microwave plasma, etc. may be used. Also, a device having two or more film formation chambers may be used. The device is preferably equipped with a vacuum pump so that each film formation chamber can be kept under vacuum. The degree of vacuum in each deposition chamber was 1×10 to 1×10 -6 Pa is preferred. An embodiment of a method for forming a vapor-deposited film using a plasma generating device will be described below. First, the first sealant layer is sent into the film-forming chamber and transported at a predetermined speed onto a cooling electrode drum via an auxiliary roll. Next, a mixed gas composition containing a film-forming monomer gas containing an inorganic oxide, oxygen gas, an inert gas, etc. is supplied from the gas supply device into the film-forming chamber, and plasma is generated on the surface resin layer by glow discharge, which is then irradiated to form a vapor-deposited film containing an inorganic oxide on the surface resin layer. The details of this formation method are disclosed in JP2012-076292A.

[0068] As an apparatus used in the method for forming a vapor-deposited film, a continuous vapor-deposited film-forming apparatus equipped with a plasma pretreatment chamber and a film-forming chamber can be used. An embodiment of a method for forming a vapor-deposited film using the apparatus will be described below. First, in the plasma pretreatment chamber, plasma is irradiated from a plasma supply nozzle onto the surface resin layer of the first sealant layer, and then, in the film formation chamber, a deposition film is formed on the plasma-treated surface resin layer. Details of this formation method are disclosed in International Publication WO2019 / 087960.

[0069] (Second sealant layer) The second sealant layer is made of a polyethylene resin. A laminate having such a configuration can be suitably used as a laminate for producing a mono-material packaging container. As the polyethylene resin, high density polyethylene resin, medium density polyethylene resin, low density polyethylene resin, linear low density polyethylene resin and very low density polyethylene resin can be used. Moreover, as the polyethylene resin, a copolymer of ethylene and another monomer can also be used. Furthermore, as the polyethylene resin, a biomass-derived polyethylene resin or a mechanically recycled or chemically recycled polyethylene resin can also be used.

[0070] The second sealant layer may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0071] The second sealant layer may have a single-layer structure or a multi-layer structure. In one embodiment, the second sealant layer includes a layer made of a linear low density polyethylene resin, a layer made of a high density polyethylene resin, and a layer made of a linear low density polyethylene resin, which can improve the heat sealability and strength.

[0072] The thickness of the second sealant layer is preferably 50 μm or more and 200 μm or less, and more preferably 70 μm or more and 150 μm or less. By making the thickness of the second sealant layer 50 μm or more, the laminate strength of the packaging container can be further improved. Furthermore, by setting the thickness of the second sealant layer to 200 μm or less, the moldability of the laminate can be improved, and the packaging container can be produced more easily.

[0073] The second sealant layer can be laminated to a vapor-deposited film or the like via a melt-extruded resin layer or an adhesive layer, which will be described below.

[0074] (Melt-extruded resin layer and adhesive layer) In one embodiment, the laminate of the present invention comprises a melt extruded resin layer or adhesive layer between the vapor deposited film and the second sealant layer. As materials for forming the melt-extruded resin layer and the adhesive layer, conventionally known resin materials and adhesives can be used. From the viewpoint of recyclability, it is preferable to form the melt-extruded resin layer and the adhesive layer using a polyethylene resin or a polyethylene-based adhesive.

[0075] The thickness of the melt-extruded resin layer and the adhesive layer is not particularly limited, and can be, for example, 1 to 30 μm.

[0076] (Barrier coat layer) The laminate of the present invention can further have a barrier coat layer provided on the vapor-deposited film. That is, by providing a barrier coat layer between the vapor-deposited film and the second sealant layer, the gas barrier properties of the laminate can be further improved.

[0077] In one embodiment, the barrier coat layer is composed of a gas barrier resin such as an ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide resins such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6), polyester resin, polyurethane resin, and (meth)acrylic resin.

[0078] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By making the thickness of the barrier coat layer 0.01 μm or more, the gas barrier property can be further improved. By making the thickness of the barrier coat layer 10 μm or less, the processability of the laminate can be improved. In addition, the laminate can be suitably used for producing a mono-material packaging container.

[0079] The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or an appropriate solvent, applying the solution or dispersion, and drying the solution.

[0080] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. By providing such a barrier coat layer on the vapor-deposited film, the occurrence of cracks in the vapor-deposited film can be effectively prevented.

[0081] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.

[0082] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.

[0083] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (mass %) Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).

[0084] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used.

[0085] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.

[0086] The thickness of the gas barrier coating film is preferably from 0.01 μm to 10 μm, and more preferably from 0.1 μm to 5 μm, which can further improve the gas barrier properties. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the barrier laminate can be improved, and the occurrence of cracks in the vapor-deposited film can be prevented. By setting the thickness of the gas barrier coating film to 10 μm or less, it is possible to obtain a laminate that can be suitably used for producing mono-material packaging containers.

[0087] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable.

[0088] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. As the acid, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used.

[0089] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.

[0090] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto the deposition film by the above-mentioned conventionally known method and dried. This drying causes the polycondensation reaction of the alkoxide and the water-soluble polymer (and the silane coupling agent if the composition contains a silane coupling agent) to proceed further, forming a layer of a composite polymer. Finally, the gas barrier coating film can be formed by heating.

[0091] (packaging container) The packaging container of the present invention comprises the above-mentioned laminate.

[0092] Specific examples of the packaging container of the present invention include laminate tubes, packaging bags, and lids.

[0093] (Laminated tube) In one embodiment, the packaging container of the present invention is a laminate tube 20. The laminated tube 20 of the present invention will be described below with reference to the drawings. Fig. 4 is a diagram showing a simplified configuration of the laminated tube 20, and Fig. 5 is a cross-sectional view taken along line aa in Fig. 4. As shown in Fig. 4, the laminated tube 20 is characterized in that it comprises a laminated tube body 21 having a head 22 and a body 23, and the body 23 is formed from the laminate 10.

[0094] (head) The head portion 22 has a shoulder portion 24 connected to one end of the body portion 23 and a sampling port portion 25 connected to the shoulder portion 24. In one embodiment, the spout portion 25 includes a thread 27 for screwing the cap 26 thereon.

[0095] In one embodiment, the head portion is made of a polyethylene resin, which can improve the recyclability of the laminated tube. The polyethylene resin may be a high-density polyethylene resin, a medium-density polyethylene resin, a low-density polyethylene resin, a linear low-density polyethylene resin, or an ultra-low-density polyethylene resin. Among these, high density polyethylene resin is preferred from the viewpoint of shape retention. Moreover, as the polyethylene resin, a polyethylene resin derived from biomass or a polyethylene resin recycled by mechanical recycling or chemical recycling can be used. The head portion may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0096] The method for producing the head is not particularly limited, and the head can be produced by a conventionally known method. For example, the head can be produced by a compression molding method or an injection molding method, and can be joined to the body.

[0097] When a laminated tube is manufactured using compression molding, the body is attached to a male mold having a convex portion on the top, the male and female molds are then placed opposite each other, and a material such as molten polyethylene resin is supplied into the male and female molds. The head is formed by compression molding and joined to one of the openings of the body, thereby producing a laminated tube consisting of a head and body. Furthermore, when a laminated tube is manufactured using injection molding, the body is attached to a male mold having a convex portion on the top, the male mold and female mold are then opposed to each other, and a material such as molten polyethylene resin is supplied from a gate, and injection molding is performed to form the head and join it to one of the openings of the body, thereby producing a laminated tube consisting of a head and body.

[0098] (Torso) In the laminate tube body of the present invention, the body portion is connected to the shoulder portion of the head portion. The body portion can be obtained by rolling the laminate into a cylindrical shape, overlapping the polyethylene resin layer of the first sealant layer and the second sealant layer, and heat-sealing the polymerized portion to form a welded portion 28. The body also includes a bottom seal 29 formed by heat sealing the opening of the rolled laminate.

[0099] Heat sealing can be performed by a conventional method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, or flame sealing.

[0100] (cap) The laminate tube may include a cap. The cap is removably attached to the extraction port of the head and serves to close the extraction port. The cap is made of a thermoplastic resin. Examples of the thermoplastic resin include polyolefin resins such as polyethylene and polypropylene, polyester, cellulose resin, and vinyl resin, with polyethylene resin being particularly preferred from the viewpoint of recyclability. Furthermore, the cap may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0101] The cap may be a screw-type cap having a groove on the inner surface thereof so as to screw into the threads of the extraction port, as shown in FIG. 5, or it may be a plug-type cap which fits into the extraction port by tapping it. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0103] Example 1 (Preparation of Laminate) Ethylene-vinyl alcohol copolymer (Kuraray Co., Ltd., EVAL E171B, density: 1.14 g / cm 3 , melting point: 165°C) Adhesive resin (Mitsui Chemicals, Inc., maleic anhydride modified polyethylene, Admer NF557, density: 0.903 g / cm 3 )and, Linear low-density polyethylene resin A (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, High density polyethylene (Prime Polymer, Hi-Zex 3300F, density: 0.949g / cm 3 )and Linear low-density polyethylene resin B (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a first sealant layer having a thickness of 125 μm. In the first sealant layer thus obtained, the surface resin layer composed of ethylene-vinyl alcohol copolymer had a thickness of 2 μm, the adhesive resin layer had a thickness of 3 μm, the polyethylene resin layer composed of linear low-density polyethylene resin A had a thickness of 30 μm, the polyethylene resin layer composed of high-density polyethylene had a thickness of 60 μm, and the polyethylene resin layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0104] A 30 nm thick aluminum vapor deposition film was formed on the surface of the surface resin layer of the first sealant layer by PVD to obtain a first sealant layer having an aluminum vapor deposition film.

[0105] As a second sealant layer, Linear low-density polyethylene resin A (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, High density polyethylene resin (Prime Polymer, Hi-Zex 3300F, density: 0.949g / cm 3 )and, Linear low-density polyethylene resin B (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a second sealant layer having a thickness of 120 μm. In the second sealant layer thus obtained, the layer composed of linear low-density polyethylene resin A had a thickness of 30 μm, the layer composed of high-density polyethylene resin had a thickness of 60 μm, and the layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0106] On the deposition film of the first sealant layer, a low-density polyethylene film (Novatec LC600A, manufactured by Japan Polyethylene Co., Ltd., density 0.918 g / cm 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 20 μm, and the layer side of the second sealant layer composed of linear low density polyethylene resin A was bonded to this melt-extruded polyethylene layer through which a laminate was produced. The polyethylene resin content in this laminate was 97% by mass.

[0107] Example 2 The ethylene vinyl alcohol copolymer was mixed with polyamide (Ube Industries, Ltd., 5033, density: 1.14 g / cm 3 A first sealant layer and a laminate were produced in the same manner as in Example 1, except that the resin composition used in Example 1 was changed to a polyurethane elastomer (melting point: 196° C.). The polyethylene resin content in this laminate was 97% by mass.

[0108] Example 3 Linear low-density polyethylene (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 ) and a compatibilizer (Dow Chemical, maleic anhydride polyethylene, Retain 3000, density: 0.87 g / cm3 ) in a ratio of 8:2 by mass was prepared.

[0109] Ethylene-vinyl alcohol copolymer (Kuraray Co., Ltd., EVAL E171B, melting point: 165°C, density: 1.14g / cm 3 )and, Adhesive resin (Mitsui Chemicals, Inc., maleic anhydride modified polyethylene, Admer NF557, density: 0.903 g / cm 3 )and, The blend resin prepared above, High density polyethylene resin (Prime Polymer, Hi-Zex 3300F, density: 0.949g / cm 3 )and, Linear low-density polyethylene (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a first sealant layer having a thickness of 125 μm. In the first sealant layer thus obtained, the surface resin layer composed of ethylene-vinyl alcohol copolymer had a thickness of 2 μm, the adhesive resin layer had a thickness of 3 μm, the layer composed of the blended resin had a thickness of 30 μm, the layer composed of the high-density polyethylene resin had a thickness of 60 μm, and the layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0110] A laminate was produced in the same manner as in Example 1, except that the first sealant layer was changed to the first sealant layer obtained as described above. The polyethylene resin content in this laminate was 97% by mass.

[0111] Example 4 The ethylene vinyl alcohol copolymer was mixed with polyamide (Ube Industries, Ltd., 5033, density: 1.14 g / cm 3 A first sealant layer and a laminate were produced in the same manner as in Example 3, except that the resin composition used in Example 3 was changed to a polyurethane elastomer (melting point: 196° C.). The polyethylene resin content in this laminate was 97% by mass.

[0112] Comparative Example 1 As the first sealant layer, Linear low-density polyethylene A (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, High density polyethylene (Prime Polymer, Hi-Zex 3300F, density 0.949g / cm 3 )and, Linear low-density polyethylene B (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a first sealant layer having a thickness of 120 μm. In the first sealant layer thus obtained, the layer composed of linear low-density polyethylene resin A had a thickness of 30 μm, the layer composed of high-density polyethylene resin had a thickness of 60 μm, and the layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0113] An aluminum vapor-deposited film having a thickness of 30 nm was formed by PVD on the surface of the layer constituted by the linear low-density polyethylene resin A of the first sealant layer, to obtain a first sealant layer having an aluminum vapor-deposited film.

[0114] A laminate was produced in the same manner as in Example 1, except that the first sealant layer was changed to the first sealant layer obtained as described above. The polyethylene resin content in this laminate was 98% by mass.

[0115] Comparative Example 2 As the first sealant layer, Linear low-density polyethylene A (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, High density polyethylene (Prime Polymer, Hi-Zex 3300F, density 0.949g / cm 3 )and, Linear low-density polyethylene B (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a first sealant layer having a thickness of 120 μm. In the first sealant layer thus obtained, the layer composed of linear low-density polyethylene resin A had a thickness of 30 μm, the layer composed of high-density polyethylene resin had a thickness of 60 μm, and the layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0116] As a substrate film, a biaxially oriented polyethylene terephthalate film (Toyobo Co., Ltd., ester film E5100) having a thickness of 12 μm was prepared. An aluminum vapor-deposited film having a thickness of 30 nm was formed on one surface of the substrate film by a PVD method to obtain a substrate film having an aluminum vapor-deposited film.

[0117] A urethane adhesive (RU004 / H1, manufactured by Rock Paint) was applied to the vapor-deposited surface of the base film and dried to form an adhesive layer with a thickness of 3 μm, and the layer composed of linear low-density polyethylene resin A of the first sealant layer was bonded to the adhesive layer via this adhesive layer.

[0118] As a second sealant layer, Linear low-density polyethylene resin A (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, High density polyethylene resin (Prime Polymer, Hi-Zex 3300F, density: 0.949g / cm 3 )and, Linear low-density polyethylene resin B (Dow Chemical, Dowlex 2098P, density: 0.926 g / cm 3 )and, The mixture was co-extruded by an inflation method to obtain a second sealant layer having a thickness of 120 μm. In the second sealant layer thus obtained, the layer composed of linear low-density polyethylene resin A had a thickness of 30 μm, the layer composed of high-density polyethylene resin had a thickness of 60 μm, and the layer composed of linear low-density polyethylene resin B had a thickness of 30 μm.

[0119] On the non-deposited film of the base film, low-density polyethylene (Nippon Polyethylene, Novatec LC600A, density 0.918 g / cm 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 20 μm, and the layer side of the second sealant layer composed of linear low density polyethylene resin A was bonded to this melt-extruded polyethylene layer through which a laminate was produced. The polyethylene resin content in this laminate was 93% by mass.

[0120] (Preparation of tube containers) The laminate obtained as described above was cut into a 120 mm wide slit using a bobbin cutter, and both ends in the width direction were overlapped so that the overlap width was about 1.5 mm, and then the overlapped ends were heat-sealed to obtain a cylindrical raw roll with a tube. The obtained raw roll was cut in the length direction to 122 mm to produce a cylindrical body portion that would become the body portion of the tube container.

[0121] The cylindrical body was attached to a mandrel for forming tube containers, and a head portion consisting of a truncated cone-shaped shoulder portion and a cylindrical extraction port portion connected to the shoulder portion was attached to one end of the cylindrical body using high-density polyethylene resin (Novatec HJ360, density 0.951 g / cm, manufactured by Nippon Polyethylene Co., Ltd.). 3 ) was molded by injection molding to produce a tube container as shown in Figure 3. The spout part at the head of the obtained tube container body had an outer diameter of 13 mm, a height of 1.5 mm, a thread was provided on the side of the spout part, and the outer diameter of the shoulder part was 38 mm.

[0122] Next, the high density polyethylene was injected into a die for forming a cap and molded to prepare a cap, thereby obtaining a tube container of the present invention.

[0123] <<Recyclability evaluation>> The recyclability of the laminates obtained in the above Examples and Comparative Examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The polyethylene resin content in the laminate was 95% by mass or more. ×: The polyethylene resin content in the laminate was less than 95% by mass.

[0124] <<Shoulder adhesive strength>> Test pieces were obtained by cutting a strip 15 mm wide from the joining point between the body and shoulder toward the bottom hem. The test piece was pulled at a test speed of 300 mm / min using a tensile tester (Orientec Co., Ltd., RTC-1310A) to measure the peel strength when the body was peeled off from the shoulder. The measurement results are summarized in Table 1.

[0125] <<Side seam strength>> The specimen was cut into strips 15 mm wide perpendicular to the side seam (overlapping area) of the body, and pulled at a test speed of 300 mm / min using a tensile tester to measure the strength at break. The measurement results are summarized in Table 1.

[0126] <<Leakage evaluation>> A cap was screwed onto the extraction opening of the tube container body, and then 120 g of commercially available toothpaste was poured into the opening of the cylindrical body, which was then heat-sealed. The tightening torque set for capping was 4.7 kg·cm. The container was left at room temperature for two weeks, and visually inspected every day to see if there was any leakage of the contents. The evaluation criteria for leakage were as follows. The evaluation results are shown in Table 1. (Evaluation Criteria) 〇: No leakage of contents was observed even after 2 weeks. ×: Leakage of contents was observed within 2 weeks

[0127] <<Gas barrier property evaluation>> The oxygen permeability (cc / m 2 ·day·atm) and water vapor transmission rate (g / m 2 ·day) was measured by the following method, and the results are summarized in Table 1.

[0128] [Oxygen permeability] Using an oxygen permeability measuring device (OX-TRAN2 / 20 manufactured by MOCON), the test piece was set so that the surface of the first sealant layer was the oxygen supply side, and the oxygen permeability was measured in an environment of 23°C and a relative humidity of 90% RH in accordance with JIS K 7126.

[0129] [Water vapor permeability] Using a water vapor permeability measuring device (MOCON, PERMATRAN-w 3 / 33), the test piece was set so that the surface of the first sealant layer was the water vapor supply side, and the water vapor permeability was measured in an environment of 40°C and relative humidity of 90% RH in accordance with JIS K 7129.

[0130] [Table 1] [Explanation of symbols]

[0131] 10: laminate, 11: first sealant layer, 12: vapor deposition film, 13: second sealant layer, 14: polyethylene resin layer, 15: surface resin layer, 16: melt-extruded resin layer or adhesive layer, 20: laminated tube, 21: laminated tube body, 22: head, 23: body, 24: shoulder, 25: pouring outlet, 26: cap, 27: thread, 28: welded portion, 29: bottom seal portion

Claims

1. A laminate (excluding laminates including a paper substrate) including at least a first sealant layer, a vapor-deposited film, and a second sealant layer in this order, The first sealant layer is a co-extrusion film having at least a polyethylene resin layer and a surface resin layer, the second sealant layer is made of a polyethylene resin; the surface resin layer of the first sealant layer contains a resin material having a melting point of 150° C. or more; A laminate, wherein the vapor-deposited film is provided on a surface resin layer of the first sealant layer.

2. The laminate according to claim 1 , wherein the surface resin layer contains a resin material having a melting point of 150° C. or higher and 265° C. or lower.

3. 3. The laminate according to claim 1, wherein the difference in melting point between the polyethylene resin and the resin material contained in the surface resin layer and having a melting point of 150° C. or higher is 20 to 80° C.

4. 4. The laminate according to claim 1, wherein the resin material of the surface resin layer is made of a polymer having a polar group.

5. The laminate according to any one of claims 1 to 4, wherein the resin material of the surface resin layer is one or more resin materials selected from ethylene vinyl alcohol copolymer, polyvinyl alcohol, polyester, nylon 6, nylon 6,6, nylon 6-nylon 6,6 copolymer, MXD nylon, and amorphous nylon.

6. The laminate according to any one of claims 1 to 5, wherein the polyethylene resin layer of the first sealant layer has a multi-layer structure.

7. The laminate according to claim 6 , wherein the polyethylene resin layer of the first sealant layer comprises at least one layer containing an unsaturated carboxylic acid-modified polyolefin resin.

8. The laminate according to any one of claims 1 to 7, further comprising a barrier coat layer having an oxygen barrier and / or a water vapor barrier between the vapor-deposited film and the second sealant layer.

9. The laminate according to any one of claims 1 to 8, which is used for a packaging container.

10. The laminate according to any one of claims 1 to 9, wherein the content of the polyethylene resin in the entire laminate is 95 mass% or more.

11. A packaging container comprising the laminate according to any one of claims 1 to 10.

12. The packaging container according to claim 11, which is a laminated tube.

Citation Information

Patent Citations

  • Paper container for packaging liquid

    JP2006306440A

  • Composite container

    JP2008162598A

  • Laminate for packaging

    WO2013004646A1

  • Recyclable, easily tearable packaging laminate having a good barrier effect, and method for production thereof

    WO2018202479A1

  • Laminate, and packaging material, packaging bag and stand-up pouch each comprising said laminate, and multi-layer substrate

    WO2019189092A1

Cited By

  • Gas barrier film, laminate, and packaging material

    JP2023001856A

  • Gas barrier film, laminate, and packaging material

    JP2023001857A

  • Gas barrier film, laminate, and packaging material

    JP2023001858A